Repackaging libraries for survival : climbing out of the box - Lee, Sul H. (Routledge LondonGB, 2012)
Begins the examination by evaluating the current state of Web-scalability in libraries. Argues that cloud computing, which has become standard practice in information technology sectors, will equally become pervasive in libraries in the future. Presents different models for providing and evaluating services in the future but contains the potential for a shift in resource allocations away from the parent library.